Mathematical modeling of gas-liquid flow in compressed air foam generation systems - Vinogradov, Stanislav; Shakhov, Stanislav; Kodryk, Anatolii; Titenko, Oleksandr; Parkhomchuk, Oleksandr (Technology audit and production reserves, 2020)
The object of research is the compression foam supply system. One of the most problematic areas in the design of compression foam supply systems is the need to obtain a certain type of foam with the necessary properties, depending on the class of fire for which it will be used to extinguish. It is necessary to take into account the technological process of foam formation, namely, the regulation of the flow of the foaming agent solution and compressed air, which are fed into the mixing chamber, where the foam is generated directly. It is important to ensure optimal parameters depending on the purpose of the foam outlet flow installation: flow rate, foam ratio and foam stability. In order to design a compression foam supply system with certain technological parameters, it is necessary to obtain these parameters analytically in advance, for which it is necessary to construct an appropriate mathematical model. In the course of the research, let’s use the Simulink graphical simulation environment (integrated into the MatLab software environment), which allows building dynamic models using separate blocks in the form of directed graphs. The structure of such a model is built on the basis of separate, independent blocks, which in themselves are separate mathematical models. New is the development of a mathematical model of a two-phase flow: a liquid phase consisting of a mixture of water with a foaming agent and a gas phase - air in the foam generator path as part of a block diagram of an installation for the case of generation of compression foam. And also the development of a scheme and communication algorithm for serially connected blocks of a common block diagram. This ensures the receipt of the calculated output data of the stationary mode of operation of the installation. The mathematical model developed in this work allows solving the following applied and scientific problems: – to carry out calculations of the input parameters of the installation, which will provide the required output parameters: flow power, frequency ratio, continuous generation time, foam resistance, determined by the purpose and features of the installation in conditions of extinguishing various types of fires; – to investigate the influence of the parameters of the foam generation insert of the installation on the expansion of the compression foam.